Exploring Prospective Physics Teachers' Perceptions of the Scientist-Teacher-Student Partnership (STSP) Program in Earth and Space Science Courses - Shelly Efwinda; Nurul Fitriyah Sulaeman; Atin Nuryadin; Dinda Ar-rizalah P. R. Putri; Tomohiro Takebayashi (Universitas Lambung Mangkurat, 2026)
The Scientist-Teachers-Students Partnership (STSP) Program offers a promising framework to bridge the gap between scientists and educators in fostering content knowledge for preservice physics teachers. This exploratory study investigates the perceptions of scientists, lecturers (teachers), and preservice physics teachers (students) regarding the implementation of the STSP program in an Earth-space science course. The research approach used was a mixed method, with qualitative data on prospective teachers' perceptions as the main data and quantitative data in the form of percentage calculations as supplementary data. The participants included one scientist, two lecturers, and 89 preservice physics teachers engaged over a 16-week semester. The program featured lectures, laboratory observations, and presentations by scientists, aiming to provide both breadth and depth in Earth-space science content. Data were collected through open-ended perception questionnaires and analyzed using coding and triangulation of responses across participant groups. Findings indicate that the STSP program effectively enhanced students' content knowledge through dynamic lectures and hands-on laboratory observations. Presentations by the scientist enriched the learning experience by integrating cutting-edge research and expert insights. All participants expressed positive perceptions, highlighting mutual benefits from the collaboration. These results underscore the potential of the STSP program as a valuable component in physics teacher preparation programs, offering a model for the interdisciplinary and collaborative learning framework.